Математична модель процесу формування та збереження колективних знань - Yasinsky, V. V.; Kapustian, O. V.; Valero, J. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2009)
Based on the introduced system of axioms, a mathematical model for forming and process of preserving collective knowledge in large educational systems is constructed and investigated. The conditions for preserving a guarateed level of collective knowledge are defined.